2023
DOI: 10.3390/nu15092057
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Breast Cancer between Western and Mediterranean Dietary Patterns

Abstract: Breast cancer is a significant public health problem globally and prevention strategies have become of great interest as its incidence rises. Exploring the connection between dietary patterns and the reduction of breast cancer risk is considered a promising approach. High levels of fiber, phytochemicals, a good antioxidant profile, and a composition of advantageous fatty acids are characteristics of healthy dietary programs such as the Mediterranean diet. This review summarized and discussed the active compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 196 publications
0
5
0
Order By: Relevance
“…Gender is considered as the most significant nonmodifiable risk factor due to sensitivity of breast cells to disruptions in the levels of hormones such as estrogen and progesterone. Contrary to intuitive beliefs, BC is hereditary in only 5-10% of cases, and it is mostly attributed to BRCA-1 and BRCA-2 gene mutation (8) . While patients with BC are often above the age of 50 (9) , the role of race and ethnicity is still very ambiguous.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Gender is considered as the most significant nonmodifiable risk factor due to sensitivity of breast cells to disruptions in the levels of hormones such as estrogen and progesterone. Contrary to intuitive beliefs, BC is hereditary in only 5-10% of cases, and it is mostly attributed to BRCA-1 and BRCA-2 gene mutation (8) . While patients with BC are often above the age of 50 (9) , the role of race and ethnicity is still very ambiguous.…”
Section: Introductionmentioning
confidence: 68%
“…Follow-up studies of BC survivors have proven the importance of regular exercise, and weight control, or even reduced cigarette and alcohol consumption (14,15) . Even dietary patterns can partially explain observed differences, as a healthy diet, such as soybean consumption and vitamin D intake, tend to lower the risk of premenopausal breast cancer (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Similar outcomes were observed when the results were classified based on menopausal status [ 52 ]. Furthermore, global studies have found similar conclusions to western diet with 14% increased BC risk [ 47 , 53 ] could be due to consumption of high amounts of red and processed meat daily ( Figure 2 ) [ 48 ].…”
Section: Dietary Patternsmentioning
confidence: 76%
“…The current analysis was based on large administrative datasets and has several limitations. First, we could not obtain detailed medical and personal data such as dietary habits 44 , smoking habits 45 or body weight 46 which are known risk factors for breast cancer and could potentially influence the association between MI and cancer. Additionally, factors like the severity of MI (e.g., Killip classification, revascularization strategies, ejection fraction data) and breast cancer staging could not be estimated in our analysis.…”
Section: Discussionmentioning
confidence: 99%